Configuration and prospects of the Piraeus shipping cluster - George K. Vaggelas; Athanasios A. Pallis (SPOUDAI - Journal of Economics and Business, 2019)
It is well verified, in both theory and practice, that clustering provides significant added value to participating companies. Shipping clusters in particular have been at the core of maritime and transport business strategies, with the most well known ones being developed around major international ports (i.e., London, New York, Singapore). This study examines the case of the shipping cluster currently existing in the major Greek port, Piraeus. Despite the fact that Greeks stand as the principal merchant fleet owners, the presence and structures of which remain unexplored, with relevant research efforts to detail it and industry initiatives to represent it being few and recent. The empirical part of the study sheds light on the size and features of the Piraeus shipping cluster, by presenting a categorisation and analysis of the several companies that are part of the shipping cluster under examination. The study also explores the rationale for the lack of a more extensive cluster development and integration at a well-known shipping centre that, among others, is linked with a dynamic port of international importance. Going beyond a 'port cluster' approach, the paper also searches for similarities and differences of the Piraeus shipping cluster with other shipping clusters. Aiming to provide input for policy development, as well as the background for further research, the paper concludes with a SWOT Analysis highlighting the initiatives that could increase the attractiveness and the functionality of the Piraeus shipping cluster.
Keywords: R12; L14; L91; 330; Cluster analysis; shipping strategies; Piraeus